Evaluation of the accuracy of traditional Pushover methods in regular RC structures - Nima Shahbazi; Reza Aghayari (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
In the traditional pushover method, which has been the noticed by seismic design code, only the effect of the first vibration mode of the structure is considered, reducing the accuracy of the results, especially in mid-rise and high-rise structures. In this article, the accuracy of traditional pushover methods was investigated in the field of short to tall reinforced concrete structures, and for this survey, the results of Nonlinear Time History (NTH) were used as a reference. The studied pushover methods include the traditional pushover method with Triangular, First-Mode and Modal lateral load pattern. To evaluate the accuracy of the mentioned methods, 4 regular special reinforced concrete moment-resisting frame constructions with the number of floors such as 3, 6, 9 and 12 were opted and designed according to ACI 318-19 and ASCE7-22 codes for the Portland city, USA. Analysis of eigenvalues, linear static, linear spectral dynamics, nonlinear statics and nonlinear time history dynamics were performed by ETABS and SeismoStruct software. The ground motions used include 10 far-fault records and 30 near-fault pulse-like records with forward-directivity. The drift ratio parameter was used as an index of deformation and the shear parameter was used as an index of force demand. It was observed that with the increase of the height of the structures, the accuracy of the investigated methods decreased and in the discussion of the maximum drift of the structure, a difference equal to 68% was calculated. In the discussion of shear distribution, the maximum difference equal to 168% was calculated. However, the traditional pushover method with the first mode and modal lateral load patterns have provided better results than the triangular lateral load pattern.